Aortic Leaflet Stresses Are Substantially Lower Using Pulmonary Visceral Pleura Than Pericardial Tissue - Chen, Ye; Lu, Xiao; Luo, Haoxiang; Kassab, Ghassan S. (Frontiers in Bioengineering and Biotechnology, 2022)
Porcine heart and bovine pericardium valves, which are collagen-based with relatively little elastin, have been broadly utilized to construct bioprosthetic heart valves (BHVs). With a larger proportion of elastin, pulmonary visceral pleura (PVP), which is the serous membrane that closely sheathes the lung surface, has greater elasticity, and could potentially serve as an advantageous biomaterial for the construction/repair of BHVs. The question of how the aortic valve’s performance is affected by its bending rigidity has attracted considerable recent attention. In this study, we employ a three-dimensional (3-D) computational fluid-structure interaction (FSI) framework to numerically investigate the aortic valve’s performance by considering three different cases with Young’s modulus E=375, 750 and 1500 kPa, respectively, which are based on the stress-strain relationships of pericardium and PVP determined by planar uni-axial tests. The results show that the higher compliance PVP aortic leaflet valve with smaller Young’s modulus E has a higher cardiac output, larger geometric opening area (GOA) and lower hemodynamic resistance. Most importantly, the aortic leaflet stresses are substantially lower within the higher compliance PVP aortic valve tissue during the systole phase, even though some stress increase is also found during the fast-closing phase due to the “water-hammer” effect similar to the pericardial tissue. The overall lower stresses in the higher compliance tissue have important implications on the potential fatigue and calcification of the PVP leaflet biomaterial.